ANALISIS TINGKAT KEPUASAN PELANGGAN DILIHAT DARI DIMENSI KUALITAS PELAYANAN DAN HARGA PT. GARUDA INDONESIA AIRLINES (PERSERO), TBK KANTOR CABANG SEMARANG - Endah Purnama Sari; Apriatni Endang Prihatini; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2014)
The development of transportation and bussines competition is increasing rapidly. They compete in providing the best service to achieve customer satisfaction. This study aims to determine the level of customer satisfaction over service quality and price of PT. Garuda Indonesia Airlines (Persero), Tbk Branch Office Semarang, that seen from the dimension of service quality consisiting of the attributes of reliability, responsiveness, assurance, emphaty, tangible and dimension of price. Type of study is qualitative descriptive. The population in this study were all customers of Garuda Indonesia Airlines, the sample of 100 respondents who used the technique accidental sampling and purposive sampling, Analysis of the data used in this study is the Importance and performance Analysis (Analysis of Importance and Performance / Satisfaction). Based on the Importance and Performance Analysis, then the conclusion that the average total for the dimension of quality of service is 89,10% include in the category are satisfied and the average total price for the dimension is 86,06% include in the category are quite satisfied. Advice can be given to the company is improving the performance of the fantasy world of service which are considered important by the customers, but still less attention from businesses